Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

What is the oblique asymptote of [tex]g(x)=\frac{x^2-3x-5}{x+2}[/tex]?

A. [tex]y = x + 5[/tex]
B. [tex]y = x - 5[/tex]
C. [tex]y = 5x[/tex]
D. [tex]y = -5x[/tex]


Sagot :

To find the oblique asymptote of the function [tex]\( g(x) = \frac{x^2 - 3x - 5}{x + 2} \)[/tex], we need to perform polynomial long division.

Step-by-Step Solution:

1. Divide the leading term of the numerator by the leading term of the denominator:
[tex]\[ \frac{x^2}{x} = x \][/tex]

2. Multiply the entire divisor [tex]\((x+2)\)[/tex] by [tex]\(x\)[/tex] and subtract this from the original numerator [tex]\((x^2 - 3x - 5)\)[/tex]:
[tex]\[ (x^2 - 3x - 5) - (x \cdot (x + 2)) = (x^2 - 3x - 5) - (x^2 + 2x) \][/tex]
Simplify this:
[tex]\[ (x^2 - 3x - 5) - (x^2 + 2x) = -5x - 5 \][/tex]

3. Divide the next term of the result (-5x) by the leading term of the divisor (x):
[tex]\[ \frac{-5x}{x} = -5 \][/tex]

4. Multiply the entire divisor [tex]\((x + 2)\)[/tex] by [tex]\(-5\)[/tex] and subtract:
[tex]\[ (-5x - 5) - (-5 \cdot (x + 2)) = (-5x - 5) - (-5x - 10) \][/tex]
Simplify this:
[tex]\[ (-5x - 5) - (-5x - 10) = 5 \][/tex]

Our quotient from the division process is [tex]\(x - 5\)[/tex] and the remainder is [tex]\(5\)[/tex].

Since we are only interested in the oblique asymptote (ignoring the remainder as [tex]\(x \to \infty\)[/tex]), we identify the oblique asymptote by the quotient we obtained:
[tex]\[ y = x - 5 \][/tex]

Therefore, the oblique asymptote of [tex]\( g(x) = \frac{x^2 - 3x - 5}{x + 2} \)[/tex] is:

[tex]\( y = x - 5 \)[/tex]

From the given choices, the correct answer is [tex]\( y = x - 5 \)[/tex].